Hydrophilic Properties of PP/CHA Nonwoven Fabrics (Journal of Fiber Bioengineering and Informatics, 2018)
This paper presents the preparation of PP/CHA melt-blown nonwoven fabric and the studies on itshydrophilic property. The property of polymer materials was investigated at the first place by differentialthermal analysis (DSC) and rheology analysis. SEM was used to study the web structure afectedby the hot air temperature. Wide-angle X-ray Diffraction (WAXD) was used to study the degree ofcrystallization of PP/CHA melt-blown nonwovens produced at different hot air temperatures. Thehydrophilic property of PP/CHA melt-blown nonwoven fabrics was studied by testing the static watercontact angle, the liquid wicking rate and the multiple liquid strikethrough time. The static contact angletest proves that hydrophilic properties were obtained by means of using the Commercial HydrophilicAdditive (CHA), while the addition of the Traditional Hydrophilic Additive (THA) did not. The liquidwicking rate test shows that PP/CHA nonwoven fabric has the highest liquid wicking rate due toits hydrophilic groups transferred to the surface and forming a hydrophilic film. The multiple liquidstrikethrough time indicates that the nonwoven fabric treated by THA loses its wettability after 3insults, while nonwovens containing 5.5% CHA remained hydrophilic even after 12 insults. It can beconcluded that PP/CHA melt-blown nonwoven fabrics have durable hydrophilic property.